1993
DOI: 10.1117/12.146998
|View full text |Cite
|
Sign up to set email alerts
|

Potential for unnecessary patient exposure from the use of storage phosphor imaging systems

Abstract: It is possible to use storage phosphor radiography (SR) devices in a manner that results in excess exposure to the patient without the operators knowledge. Because these SR systems have an automatic correction for the final optical density (OD) of the image, the technologist and radiologist will not be able to use excessive blackness of the image as a sign of overexposure. Tests reported here demonstrate that it is possible to obtain images of a chest phantom that appear acceptable with a 32 times difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…While this has resulted in fewer repeats due to overexposed images, [9][10][11]16 it has also resulted in a phenomenon known as dose creep. 17,18 Because of the automatic adjustment of grayscale in digital imaging, until the limit of adjustment is reached, overexposed images have a more pleasing appearance than underexposed images. Technologists respond to feedback from radiologists who naturally prefer less noisy images.…”
Section: -4mentioning
confidence: 99%
“…While this has resulted in fewer repeats due to overexposed images, [9][10][11]16 it has also resulted in a phenomenon known as dose creep. 17,18 Because of the automatic adjustment of grayscale in digital imaging, until the limit of adjustment is reached, overexposed images have a more pleasing appearance than underexposed images. Technologists respond to feedback from radiologists who naturally prefer less noisy images.…”
Section: -4mentioning
confidence: 99%
“…Accordingly, in digital imaging modalities there is a tendency to increase the amount of radiation used to avoid this problem (dose creep) (92,93). Increasing doses in this manner does not necessarily improve diagnostic performance, but will always increase the patient dose.…”
Section: Keep Patient Doses As Low As Reasonably Achievable (Alara)mentioning
confidence: 99%
“…Computed radiography and digital radiography systems have substantial exposure latitude, which, combined with modern reliable AEC systems, should always result in optimum images at doses that are as low as reasonably achievable, with minimal repeat rates. However, in the absence of counter-measures, such systems actually exhibit the phenomenon of exposure creep [4][5][6][7]. In addition, historical studies of exposure settings and patient doses have shown that there is a wide spread in these quantities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, each 15% change in kVp was equivalent to a factor of two in mAs, or in mA or time individually. The 15% value is derived from the reasonable approximation that the energy absorbed by the image receptor is proportional to kVp 5 and noting that 1.15 5 = 2.0 [2], leading to the well-known 15% rule [3].…”
Section: Introductionmentioning
confidence: 99%